The Effect of Using Quizlet on Students’ Vocabulary Mastery in Junior High School - Indri Kusuma Dewi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The teaching and learning process in learning English as a second language involves mastering vocabulary (Moeller, 2009). Without grammar, there is very little that can be expressed; without vocabulary, there may not be anything that can be described (Thornbury, 2002). According to Merriam-Webster Dictionary (2002), vocabulary changes the language to make it more interesting and easier to understand by choosing the right words. The words that are used by a person are usually arranged alphabetically, to explain or define everything means that vocabulary is the total number of words in a particular language that a person uses or knows. One of the linguistic attributes that affects communicative ability is vocabulary knowledge. A quasi-experimental research design with a posttest-only design was employed in this study, as its primary objective was to investigate whether using Quizlet has a significant impact on students’ vocabulary mastery. The population of this research was seventh-grade students of the Junior High School in Banyuwangi. The research participants were determined based on the result of the homogeneity test, which showed that the population of the research was heterogeneous; hence, the experimental class and control class were determined by lottery. The number of participants was 65 in total. The experimental group consisted of 32 students, meanwhile the control group consisted of 33 students. The participants of this research were selected by choosing the similarity mean, VII D as the experimental class, meanwhile VII A as the control class. The experimental class received treatment by using Quizlet, while the control class used paper-based media.
Reupload File Repository 15 April 2026_Yudi
Keywords: Effectiveness; Using Quizlet; Students' Vocabulary Mastery